A novel technique for micro-hole forming on skull with the assistance of ultrasonic vibration. (April 2016) - Li, Zhe; Yang, Daoguo; Hao, Weidong; Wu, Tiecheng; Wu, Song; Li, Xiaoping
Abstract: Micro-hole opening on skull is technically challenging and is hard to realize by micro-drilling. Low-stiffness of the drill bit is a serious drawback in micro-drilling. To deal with this problem, a novel ultrasonic vibration assisted micro-hole forming technique has been developed. Tip geometry and vibration amplitude are two key factors affecting the performance of this hole forming technique. To investigate their effects, experiment was carried out with 300 μm diameter tools of three different tip geometries at three different vibration amplitudes. Hole forming performance was evaluated by the required thrust force, dimensional accuracy, exit burr and micro-structure of bone tissue around the generated hole. Based on the findings from current study, the 60° conically tipped tool helps generate a micro-hole of better quality at a smaller thrust force, and it is more suitable for hole forming than the 120° conically tipped tool and the blunt tipped tool. As for the vibration amplitude, when a larger amplitude is used, a micro-hole of better quality and higher dimensional accuracy can be formed at a smaller thrust force. Findings from this study would lay a technical foundation for accurately generating a high-quality micro-hole on skull, which enables minimally invasive insertion of a microelectrode into brain for neural activity measuring. Graphical abstract: Highlights: A pioneering technique for micro-hole forming on skull bone. Generation of 300 μm diameter micro-holes on skull. High-quality and high-precision micro-hole forming.